2012
DOI: 10.1111/j.1475-6811.2012.01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Romantic relationships in early adulthood: Influences of family, personality, and relationship cognitions

Abstract: Two hundred and sixty‐five participants and their romantic partners were involved in a prospective, longitudinal, and multimethod study during the transition from adolescence to adulthood. Guided by the development of the early adult romantic relationships (DEARR) model (Bryant & Conger, 2002), the research (a) investigated mid‐adolescent family experiences and individual differences in personality as predictors of qualities in the early adult romantic union and (b) evaluated the degree to which marital belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…Steinberg (2001) notes that parenting during adolescence involves a unique and influential developmental context because it represents autonomy-related changes and important negotiations in the parent-child relationship. Similarly, earlier findings from the longitudinal study used for the present analyses showed that nurturant-involved parenting practices during adolescence predicted greater warmth and support and lower hostility toward a romantic partner in adulthood (Conger, Cui, Bryant, & Elder, 2000;Masarik et al, 2013). For example, a study by Whitton et al (2008) showed that positive engagement and hostility expressed by parents toward their adolescent child during family conflict resolution tasks predicted positive engagement and hostility expressed by offspring toward their spouses in a marital conflict task 17 years later.…”
Section: Parenting and Genetic Influences On Romantic Relationship Desupporting
confidence: 71%
“…Steinberg (2001) notes that parenting during adolescence involves a unique and influential developmental context because it represents autonomy-related changes and important negotiations in the parent-child relationship. Similarly, earlier findings from the longitudinal study used for the present analyses showed that nurturant-involved parenting practices during adolescence predicted greater warmth and support and lower hostility toward a romantic partner in adulthood (Conger, Cui, Bryant, & Elder, 2000;Masarik et al, 2013). For example, a study by Whitton et al (2008) showed that positive engagement and hostility expressed by parents toward their adolescent child during family conflict resolution tasks predicted positive engagement and hostility expressed by offspring toward their spouses in a marital conflict task 17 years later.…”
Section: Parenting and Genetic Influences On Romantic Relationship Desupporting
confidence: 71%
“…A warm and cohesive family climate fosters individuals with better differentiated self, constructive communication patterns, and less hostile-aggressive behaviors, which are closely related to better romantic relationship functioning in young adulthood (Fosco et al 2016; Holman and Busby 2011). Adolescents in more cohesive and organized families are more likely to form close, intimate, and satisfying significant relationships later in life (e.g., Larson et al 2001; Masarik et al 2013). Adolescents who live in families with a more positive climate are thought to develop a more positive interpersonal style which carries over into later romantic relationships (Ackerman et al 2013; Whitton et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Family of origin factors have a significant influence on young adult romantic relationship success (Bryant & Conger, ; Cui & Fincham, ; Cui, Fincham, & Pasley, ; Donnellan, Larsen‐Rife, & Conger, ; Whitton, Rhoades, Stanley, & Markman, ; Yoshida & Busby, ). Several individual and relational mechanisms through which the family of origin shape young adult romantic relationship quality have also been explored and include mental health (Anderson et al, ; Johnson & Galambos, ), marital beliefs (Masarik et al, ), relationship efficacy (Cui et al, ), commitment (Cui & Fincham, ), and couple interactions (Cui & Fincham, ; Cui et al, ; Donnellan et al, ; Johnson, Nguyen, Anderson, Liu, & Vennum, ). While this literature is robust, there are additional mechanisms yet to be explored that may also explain linkages between family of origin factors and relationship outcomes in young adulthood.…”
mentioning
confidence: 99%
“…which the family of origin shape young adult romantic relationship quality have also been explored and include mental health (Anderson et al, 2014;Johnson & Galambos, 2014), marital beliefs (Masarik et al, 2013), relationship efficacy (Cui et al, 2008), commitment (Cui & Fincham, 2010), and couple interactions (Cui & Fincham, 2010;Cui et al, 2008;Donnellan et al, 2005;Johnson, Nguyen, Anderson, Liu, & Vennum, 2015). While this literature is robust, there are additional mechanisms yet to be explored that may also explain linkages between family of origin factors and relationship outcomes in young adulthood.…”
mentioning
confidence: 99%
See 1 more Smart Citation